PELATIHAN DAN PEMBANGUNAN RUMAH KOMPOS: PEMBERDAYAAN MASYARAKAT DESA PULAU BANJAR KARI, KUANTAN SINGINGI, MENUJU DESA MANDIRI BINAAN UNIVERSITAS RIAU [WORKSHOP AND DEVELOPING OF COMPOSTING HOUSE: COMMUNITY DEVELOPMENT IN DESA PULAU BANJAR KARI, KUANTAN SANGIGI, TOWARD UNIVERSITY OF RIAU PILOTED-VILLAGE] - Hilwan Yuda Teruna; Christine Jose; Yum Eryanti; Ganis Fia Kartika; Yuharmen -; Rudi Hendra; Yuli Haryani (Jurnal Sinergitas PKM & CSR, 2018)
The piloted-village grant of University of Riau is a community development program which is granted for University of Riau academics to build a village in the sectors of economics and health. In this program, Desa Pulau Banjar Kari was chosen due to their active in developing their agricultural and health. In this program, the academic team from University of Riau supervised the community how to prepare and produce organic fertilizer based on Effective Microorganism technology (active EM, EM5, bokashi, and fermented-plant extracts). The products were applied into their garden as well as for commercial. Furthermore, the product was applied in increasing medicinal plants values.  In order to achieve the aim of this program, the team built a home for the preparation of the product, providing all the equipment and materials and as well as knowledge transfer by doing workshop. The monitoring and evaluation of the programs were done by visiting the area and do evaluation such as observation of the product, the sustainability of product and medicinal plants garden (TOGA). In conclusion, the program was successfully where the people in Desa Pulau Banjar Kari is able to produce the product by themselves and they have been transferring the knowledge to students and people from different villages.